Cytokinin modulates proteomic, transcriptomic and growth responses to temperature shocks in Arabidopsis - Cerný, Martin; Jedelský, Petr L; Novák, Jan; Schlosser, Andreas; Brzobohatý, Břetislav (Plant, cell & environment, 2014)
As sessile organisms, plants must sense environmental conditions and adjust their growth and development processes accordingly, through adaptive responses regulated by various internal factors, including hormones. A key environmental factor is temperature, but temperature-sensing mechanisms are not fully understood despite intense research. We investigated proteomic responses to temperature shocks (15 min cold or heat treatments) with and without exogenous applications of cytokinin in Arabidopsis. Image and mass spectrometric analysis of the two-dimensionally separated proteins detected 139 differentially regulated spots, in which 148 proteins were identified, most of which have not been previously linked to temperature perception. More than 70% of the temperature-shock response proteins were modulated by cytokinin, mostly in a similar manner as heat shock. Data mining of previous transcriptomic datasets supported extensive interactions between temperature and cytokinin signalling. The biological significance of this finding was tested by assaying an independent growth response of Arabidopsis seedlings to heat stress: hypocotyl elongation. This response was strongly inhibited in mutants with deficiencies in cytokinin signalling or endogenous cytokinin levels. Thus, cytokinins may directly participate in heat signalling in plants. Finally, large proportions of both temperature-shock and cytokinin responsive proteomes co-localize to the chloroplast, which might therefore host a substantial proportion of the temperature response machinery.
Keywords: mutace; proteome; biologické modely; Heat-Shock Response; temperature; geneticky modifikované rostliny; Arabidopsis Proteins; teplota; proteom; heat; Plants, Genetically Modified; Proteome; hormones; Models, Biological; hypocotyl elongation; Mutation; hypokotyl; cytokininy; Cytokinins; proteiny huseníčku; Hypocotyl; Temperature; cold; rostlinné geny; fosforylace; metabolismus sacharidů; Arabidopsis thaliana; reakce na tepelný šok; Arabidopsis; transkriptom; Transcriptome; Carbohydrate Metabolism; Genes, Plant; Phosphorylation